Macroeconomic and Microeconomic Effects on Tax Avoidance in IDX Energy Companies 2022-2024 - Sheyla Zefanya Asmarakanti; Omi Pramiana (Proceeding International Conference on Digital Education and Social Science, 2025)
Tax avoidance is a common problem for many organizations, including those in the energy sector. There are a number of economic factors, both big and little, that might affect tax evasion. This study seeks to examine the impact of macroeconomic factors, quantified by inflation and currency rates, on tax avoidance, as well as the influence of microeconomic factors, assessed by leverage and firm size, on tax avoidance. The research methodology employs a quantitative descriptive technique. Multiple linear regression is used to analyze the data. The findings indicate that inflation, leverage, and business size exert a substantial positive influence on tax avoidance, signifying that increased inflation, leverage, and firm size correlate with heightened tax avoidance by the organization. In addition, changes in currency exchange rates do not seem to alter the level of tax avoidance by corporations.